The impact of enabling the effectiveness of the work of the audit committees in private commercial banks (A survey study of the views of a sample of the objective of the inspection bodies represented by the Central Bank and the Securities Commission and e - سعود عبد الرضا حسن; حمد سلمان رائد فاضل; الغرباوي حازم عبد عزيز (Journal of Economics and Administrative Sciences, 2019)
The aim of this study is to identify the effect of enabling the effectiveness of the work of the audit committees in private commercial banks and to identify the extent of awareness of the importance of empowerment in the work of these committees, especially as it is known that these committees, especially the inspection committees that go to private banks and from various sources including committees of the Central Bank of Iraq Committees of the Securities Commission and finally committees of the external audit offices, through an analysis of the determinants of empowerment in the performance of the most important work of the audit committees, namely: supervising the process of preparing reports, supervising the system of internal control and risk management, And the independence of the internal auditor, to strengthen the effectiveness and independence of the external auditor In order to achieve these objectives, a questionnaire form consisting of two lists prepared for this purpose was designed to be distributed to a sample of banks and a sample of the audit offices and a sample from the Securities Commission final, The analysis of the data in the SPSS program examined the hypotheses and the research reached the importance of the dimensions of empowerment in the work of the audit committees by 84%. The most important of the dimensions of empowerment is motivation, training and knowledge on the work of the audit committees, while the second form, Among the three independent samples are the Central Bank, the Securities Commission and the external audit offices, which are considered inspection committees on these private banks. The impact of empowerment is on supervision of the reporting process (77%). The impact of empowerment in the second dimension is the supervision of the internal control and risk management system (80%). The third dimension was to strengthen the effectiveness and independence of the internal auditor (84%). The fourth dimension is to strengthen the effectiveness and independence of the external auditor (79%). There were no significant differences between the three independent samples according to the t-test of the independent samples and their consensus on the overall effect of the overall audit ability by (79%). The research ended with several recommendations including: Giving importance to the audit committees by the administration, As well as the selection of members according to the standard of professionalism and experience and the need to emphasize the reliance on an integrated system of control and scrutiny and motivation of the principle of self-control by members, as well as highlighting the system of accountability and accountability by the Audit Committees, and to find a real and effective existence of the Audit Committees besides Mam achieving effective communication to cancel all the gaps that may occur between the administration and the expectations of users and external auditors, and that the necessary decisions and taking them as the closest to the operational reality of the banks